Choice and ground for direction of energy efficiency increasing for Ukrainian buildings and facilities - Yeromin, Andriy; Kolosov, Aleksandr (Technology audit and production reserves, 2017)
The object of research is a complex thermal modernization of a building or structure, namely its tandem as part of a heating system and facade thermal insulation. One of the most problematic places is not enough to study the features of the thermal regime in the operation of buildings and structures, as well as the lack of optimization approaches to carrying out thermal modernization. In the course of the study, a comprehensive approach to the solution of the set tasks is used, including economic and statistical analysis, analysis of world experience and synthesis of results and retrospectives, a historical, evolutionary and logical approach. System theory and system analysis are also used to identify strategic prospects for a significant reduction in the energy consumption of existing Ukrainian buildings and structures and, in the future, dissemination of the results obtained to foreign buildings and facilities that have similar energy efficiency challenges. Based on the analysis of patent information sources, innovative organizational and technical solutions for the thermal modernization of Ukrainian buildings and structures are proposed. In particular, it is proposed to introduce new elements in the system of complex thermal modernization in the form of new transit pipelines of a two-pipe system of central water heating. No less important task is the optimal placement of new transit pipelines of a two-pipe system of central water heating with reference to the locations of existing heating appliances. The expected positive effect is achieved due to the provision of the possibility to take into account and regulate the consumption of heat by consumers taking into account the operational factors of maintaining the specified temperature regime inside the heated premises of buildings and structures. Due to this, it is possible to increase the efficiency of using heat energy in the proposed system of central water heating of premises and to reduce the consumption of thermal energy for maintaining the optimal conditions for living in a residential area. And it is possible in almost all climatic zones, where there is a need for thermal modernization, especially for housing, mainly the period of construction until the 90s of the last century.